Counter Institution : Activist Estates of the Lower East Side - Bagchee, Nandini (Empire State Editions, an imprint of Fordham University Press, 2018)
Counter Institution is a history of three re-purposed buildings in the Lower East Side--Peace Pentagon, ABC No Rio, and El Bohio--that have been used by activists as their headquarters to launch various actions over the past forty years.